Recent developments in forward osmosis membrane bioreactors: a comprehensive review - Eyvaz, Murat; Aslan, Taha; Arslan, Serkan; Yüksel, Ebubekir; Koyuncu, Ismail (Desalination Publ, 2016)
Forward osmosis or osmotic membrane bioreactor (FOMBR) has attracted great attention for wastewater treatment and reuse since conceptually introduced as a process. It has been proposed to reduce the high energy consumption in the conventional MBR, has lower membrane fouling propensity, and produce higher quality water. Moreover, RO process can be used after FOMBR to reconcentrate the diluted DS to be used for FO again. Besides significant advantages, when compared to conventional MBRs; lower water flux, concentration polarization, and salt accumulation because of high retention of FO in the bioreactor still remains as major drawbacks and challenges of FOMBR systems that need to be solved. In the last few years, many advances in development of FOMBR are stated to overcome the drawbacks of the system. The researches focused on manufacturing of high performance FO membranes and orientation, utilizing various different draw solutions providing required osmotic pressure and minimum reverse salt flux, and recently hybrid systems to alleviate the salt accumulation in bioreactor. However, the main critical challenges of FOMBR have not been completely resolved yet. This paper reviews the design and applications of FOMBR process in wastewater treatment. Particular focus was given to reverse salt flux and effects of the system performance; recent developments in FOMBR applications from beginning till today are reported.
Keywords: Forward osmosis; Membrane bioreactor; Draw solution; Salt accumulation